Oxytocin Increases the Perceived Value of Both Self- and Other-Owned Items and Alters Medial Prefrontal Cortex Activity in an Endowment Task - Zhao, Weihua; Geng, Yayuan; Luo, Lizhu; Zhao, Zhiying; Ma, Xiaole; Xu, Lei; Yao, Shuxia; Kendrick, Keith M. (Frontiers in Human Neuroscience, 2017)
The neuropeptide oxytocin (OXT) can influence self-processing and may help motivate us to value the attributes of others in a more self-like manner by reducing medial prefrontal cortex (mPFC) responses. We do not know however whether this OXT effect extends to possessions. We tend place a higher monetary value on specific objects that belong to us compared to others, known as the “endowment effect”. In two double-blind, between-subject placebo (PLC) controlled experiments in subjects from a collectivist culture, we investigated the influence of intranasal OXT on the endowment effect, with the second study incorporating functional magnetic resonance imaging (fMRI). In the task, subjects decided whether to buy or sell their own or others’ (mother/father/classmate/stranger) possessions at various prices. Both experiments demonstrated an endowment effect in the self-owned condition which extended to close others (mother/father) and OXT increased this for self and all other-owned items. This OXT effect was associated with reduced activity in the ventral mPFC (vmPFC) in the self-owned condition but increased in the mother-condition. For the classmate- and stranger-owned conditions OXT increased activity in the dorsal mPFC (dmPFC). Changes in vmPFC activation were associated with the size of the endowment effect for self- and mother-owned items. Functional connectivity between the dmPFC and ventral striatum (VStr) was reduced by OXT in self- and mother-owned conditions and between vmPFC and precuneus in the self-condition. Overall our results show that OXT enhances the endowment effect for both self- and other-owned items in Chinese subjects. This effect is associated with reduced mPFC activation in the self-condition but enhanced activation in all other-conditions and involves differential actions on both dorsal and ventral regions as well as functional connectivity with brain reward and other self-processing regions. Overall our findings suggest that OXT increases the perceived value of both self- and other-owned items by acting on neural circuitry involved in self-processing and reward.